Konjungsi yang Berasal dari Kata Berafiks dalam Bahasa Indonesia - Amin, Mujid Farihul (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
Conjunctions are derived from the basic + affixes, broadly grouped into two, namely the coordinative conjunctions and subordinating conjunctions. Coordinative conjunctions are derived from the basic + affixes is melainkan, padahal, and sedangkan. Subordinating conjunctions are derived from the basic + affixes can be specified by its meaning as follows: 1) a significant time sebelum, sesudah, setelah, selagi, sewaktu,  sedari, selama, sehabis, selepas, seusai.  2) meaningful terms: provided asalkan, jikalau, dan manakala, 3) meaningful supposition: seandainya, seumpama, sekiranya andaikan, andaikat, 4) means konsesif: meskipun, walaupun, bagaimanapun, kendatipun, biarpun, sekalipun, sungguhpun, and 5) a meaningful result: sehingga, makanya.